Natural-Fiber-Reinforced Chitosan, Chitosan Blends and Their Nanocomposites for Various Advanced Applications - Ilyas R.A.; Aisyah H.A.; Nordin A.H.; Ngadi N.; Zuhri M.Y.M.; Asyraf M.R.M.; Sapuan S.M.; Zainudin E.S.; Sharma S.; Abral H.; Asrofi M.; Syafri E.; et al. (MDPI, 2023)
Biodegradability; Biopolymers; Blending; Chemical stability; Costs; Durability; Film preparation; Nanocellulose; Nanocomposites; Natural fibers; Reinforcement; Wastewater treatment; Advanced applications; Biodegradable material; Chitosan blends; Chitosan nanocomposite; Composite products; Eco-friendly materials; Environmental concerns; Green composites; Natural fiber composites; Natural fiber reinforced; Chitosan; Biodegradability; Costs; Durability; Mixing; Natural Fibers; Reinforcement